2023
DOI: 10.5194/isprs-archives-xlviii-1-w1-2023-273-2023
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Accuracy of as-Built Modelling From Slam-Based Point Clouds: Preliminary Results

A. Matellon,
E. Maset,
D. Visintini
et al.

Abstract: Abstract. Nowadays, portable Mobile Mapping Systems (MMSs) and robotic mapping platforms leveraging on Simultaneous Localization and Mapping (SLAM) methods are gaining increasing attention for architectural and construction surveying, representing an efficient solution for geometric data acquisition for scan-to-BIM purposes. However, the applicability of standard modelling workflows and the accuracy of Building Information Models (BIM) that can be obtained from SLAM-based point clouds is still an open question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…While "scanning-whilenavigating" approaches like those in [19,20] are efficient, they rely heavily on SLAM algorithms, which produce noisy point clouds. This makes them unsuitable for architectural detail capture, unlike automated TLS-based approaches [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While "scanning-whilenavigating" approaches like those in [19,20] are efficient, they rely heavily on SLAM algorithms, which produce noisy point clouds. This makes them unsuitable for architectural detail capture, unlike automated TLS-based approaches [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [12][13][14][15] have explored different scanning approaches and devices for evaluating point cloud quality in 3D as-built BIM model creation. These studies have suggested that point clouds generated by low-quality LiDAR devices using SLAM are often too sparse and inaccurate.…”
Section: Related Workmentioning
confidence: 99%